Nano-rings with a handle – Synthesis of substituted cycloparaphenylenes - Tran-Van, Anne-Florence; Wegner, Hermann A. (Beilstein Journal of Nanotechnology, 2014)
The research of cycloparaphenylenes (CPPs), the smallest armchair carbon nanotube, has been a quest for the past decades which experienced a revival in 2008 when the first synthesis was achieved. Since then CPPs with various ring sizes have been realized. The incorporation of substituents and the synthesis of CPPs with building blocks different from phenyl rings bear challenges of their own. Such structures, however, are highly interesting, as they allow for an incorporation of CPPs as defined nano-objects for other applications. Therefore, this review provides a status report about the current efforts in synthesizing CPPs beyond the parent unsubstituted oligo-phenylene structure.
Keywords: aromatic compounds; carbon nanotubes; cycloparaphenylene; organic synthesis